2011
DOI: 10.1111/j.1743-6109.2010.02191.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hypertension, Aging, and Antihypertensive Treatment on the Morphology of the Pudendal Artery

Abstract: Introduction Aging and hypertension increase the risk of erectile dysfunction (ED) and cardiovascular disease. Arterial insufficiency is likely a primary factor in hypertension-related ED. Given the dominance of internal pudendal arteries in controlling penile vascular resistance, pathological changes in this vessel would be critical for inducing ED in aged hypertensives. Aim We assessed the age-related impact of hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 66 publications
2
17
0
Order By: Relevance
“…Recent studies have shown that the PA contributes approximately 70% of total pudendal-penile vascular resistance, whereas the intrapenile vasculature contributes less than 25% of total resistance in this bed (Manabe et al, 2000). In addition, it has been demonstrated that optimal erection requires vasodilation of both prepenile arteries, such as the PA, as well as intrapenile arteries (Manabe et al, 2000;Hale et al, 2009;Hannan et al, 2011). To date, no studies have characterized the contribution of adenosine and its receptors in the regulation of the PA vascular tone.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the PA contributes approximately 70% of total pudendal-penile vascular resistance, whereas the intrapenile vasculature contributes less than 25% of total resistance in this bed (Manabe et al, 2000). In addition, it has been demonstrated that optimal erection requires vasodilation of both prepenile arteries, such as the PA, as well as intrapenile arteries (Manabe et al, 2000;Hale et al, 2009;Hannan et al, 2011). To date, no studies have characterized the contribution of adenosine and its receptors in the regulation of the PA vascular tone.…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of ACE inhibitor in hypertensive rats may be not as benefi cial in prevention of neointimal thickening as in normotensive ones [13]. Further, the effi cacy of such therapy may depend on age [14], way of application [15] and degree of atherosclerosis [16]. Unfortunately, some studies of primate or human tissues did not confi rm the benefi cial effects of this medication on the long-term changes of the vascular architecture [7,17].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a significant, but not strong, increase in collagen production was seen in 80-week-old Wistar rats (Lin, Tsai, Lin, Lin, & Chow, 2001), as were degeneration of the elastic fibers in 27-month-old Wistar rats (Calabro et al, 1996) and alterations in the cavernosal smooth muscle content and function in 24-to 30-month-old Wistar rats (Dahiya et al, 1999;Wespes, 2002). Hannan et al (2001) showed that erectile responses declined significantly in 77-week-old spontaneously hypertensive rats compared with 15-week-old spontaneously hypertensive rats (SHRs) and Wistar-Kyoto rats (WKRs). Vascular aging in SHRs exhibited prominent remodeling with marked proliferation and disruption of internal elastic lamina (Hannan et al, 2001).…”
Section: Age-induced Edmentioning
confidence: 99%
“…Hannan et al (2001) showed that erectile responses declined significantly in 77-week-old spontaneously hypertensive rats compared with 15-week-old spontaneously hypertensive rats (SHRs) and Wistar-Kyoto rats (WKRs). Vascular aging in SHRs exhibited prominent remodeling with marked proliferation and disruption of internal elastic lamina (Hannan et al, 2001). In fact, studies have confirmed that SHRs average approximately 30% lower ICP than age-matched WKRs (Behr-Roussel et al, 2003).…”
Section: Age-induced Edmentioning
confidence: 99%